Prenatal alcohol exposure affects renal function in overweight schoolchildren: birth cohort analysis - Correia-Costa, Liane; Schaefer, Franz; Afonso, Alberto Caldas (Pediatric nephrology, 2020)
Prenatal ethanol exposure has been shown to reduce nephron endowment in animal models, but the effect of alcohol during human pregnancy on postnatal kidney function has not been explored. We aim to investigate the potential association of maternal alcohol consumption during pregnancy with the offspring renal function, considering potential confounding by intrauterine growth and children’s current nutritional status.